A Study on Translation Methods and Strategies in the English Translation of the Li Sao by Yang Xianyi and Gladys Yang - Yang, Weiwei (Classical Literature, 2024)
The poem Li Sao in Chu Ci first created the form of the unique genre “Sao Ti” in Chinese literature, displaying a positive romantic spirit. It has been included in textbooks multiple times and has had a significant impact on the development of Chinese literature. After the Han Dynasty, later literati always highly respected Qu Yuan. The quality of the English translation of Li Sao, as a representative chapter of the Chu Ci, directly reflects the quality of the selected translation. This article takes the English translation of Li Sao by Yang Xianyi and Gladys Yang as the starting point, analyzes its translation methods from three levels: rhythm, rhetoric, and culturally-loaded words, and explores the translation strategies the translators adopt. This will provide valuable reference experience for translators and have a certain guiding significance for the English translation of literary classics in China.